Numerical analysis of embankments on soft soils incorporating vertical drains - J. L. Borges (2009)
The use of vertical drains in embankments on soft soils is one of the most adequate techniques when the main purpose is to accelerate the consolidation. In the paper, three-dimensional behaviour of an embankment on soft soils incorporating vertical drains (geosynthetic band drains) is modeled with a computer program based on the finite element method. The program incorporates the Biot consolidation theory (coupled analysis) with constitutive relations simulated by the p-q- critical state model. The same problem without drains (two-dimensional analysis) is also performed. Special emphasis is given to the analysis, during and after the construction period, of the excess pore pressures, settlements, horizontal displacements and stress levels.